2021
DOI: 10.3390/toxins13080538
|View full text |Cite
|
Sign up to set email alerts
|

The Natterin Proteins Diversity: A Review on Phylogeny, Structure, and Immune Function

Abstract: Since the first record of the five founder members of the group of Natterin proteins in the venom of the medically significant fish Thalassophryne nattereri, new sequences have been identified in other species. In this work, we performed a detailed screening using available genome databases across a wide range of species to identify sequence members of the Natterin group, sequence similarities, conserved domains, and evolutionary relationships. The high-throughput tools have enabled us to dramatically expand t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 119 publications
(143 reference statements)
1
23
0
Order By: Relevance
“…The proteomic analyses revealed proteins that are involved in the immune response, and are very similar to the proteins related to the sting, and also similar to proteins described in fishes from Teleostei class, indicating that the epidermal secretions of stingrays could be more related to an innate immune system than with a venom delivery system [146]. This hypothesis was recently reinforced in a work that analyzed the genomic data of a venomous fish and associated the presence of aerolysin (considered as a toxin) with the immune system [147].…”
Section: Stingraysmentioning
confidence: 65%
“…The proteomic analyses revealed proteins that are involved in the immune response, and are very similar to the proteins related to the sting, and also similar to proteins described in fishes from Teleostei class, indicating that the epidermal secretions of stingrays could be more related to an innate immune system than with a venom delivery system [146]. This hypothesis was recently reinforced in a work that analyzed the genomic data of a venomous fish and associated the presence of aerolysin (considered as a toxin) with the immune system [147].…”
Section: Stingraysmentioning
confidence: 65%
“…in addition to the fish species where these proteins were initially discovered and characterized, several insects, birds, plants and others (Lima et al, 2021). The phylogenetic distance from these proteins could have been partly due to the presence of agglutinin domains, instead of the predominant amaranthin AA lectin domains, in the N-terminal end of the AhN4L-1 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Natterins and nattering-like proteins are characterized by the presence of an aerolysinlike pore-forming domain characteristic of Aeromonas species (Szczesny et al, 2011). These proteins were initially described in Thalassophryne nattereri a venomous fish species; now, their presence has been reported several others Eukaryotic organisms, including arbuscular mycorrhizal fungi, oysters, insects, birds and plants (Lopes-Ferreira et al, 1998;Tamura et al, 2011;Xue et al, 2012;Gacesa et al, 2015;Gudbrandsson et al, 2015;Unno et al, 2016;Rajan et al, 2017;Lima et al, 2021). They are considered to play a role as host defense molecules against pathogens in some of these organisms (Chen et al, 2018), whereas Natterin-4 genes have been found to be responsive to severe water-deficit stress (WDS) in maize (Shao et al, 2015;Jin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The T. nattereri envenomation in humans and the recapitulation of the injury in mice have been extensively studied by our group [24][25][26]. We identified in the Natterin group of venom toxins the aerolysin proteins being responsible for the main effects of envenomation [27,28], and their immunopharmacological activities were determined [29][30][31][32]. Besides the Natterin proteins, T. nattereri venom also contains Nattectin, a lectin with Ca 2+independent hemagglutinating and immunomodulatory activities [4].…”
Section: Discussionmentioning
confidence: 99%
“…Balb/c mice were intraperitoneally injected with TmC4-47.2 at 10 µg in 500 µL, according to Lima et al [32]. As a negative control, mice were injected i.p.…”
Section: Acute Inflammation Induced By Tmc4-472mentioning
confidence: 99%